(untitled) (Asian Journal of Medical and Biological Research, 2016)
The experiment was conducted on in vitro regeneration of tomato at the Plant Biotechnology Laboratory, Department of Horticulture, Patuakhali Science and Technology University, Patuakhali. The objective was to develop an efficient regeneration protocol in tomato through callus induction for subsequent plantlet regeneration. Seeds were inoculated on MS medium where germination rate was 78.4%. The stems of in vitrocultured seedlings were used as explants. Different concentrations and combinations of growth regulators were added to MS medium to observe their efficacy on callus induction, shoot initiation and root formation. Stem explants cultured on MS medium fortified with 2 mg/L BAPgave the highest number of shoots (3.0) at 45 DAC. Among the concentrations of PGRs, 0.25 mg/L IAA produced the highest length (4.064 cm) of plantlets, number (5.0) of leaves and fresh weight (0.663 g) of plantlets with the stem explants at 45 DAC. The concentration of 0.5 mg/L IAA produced the highest number (21.00) of roots/plantlet, length (7.676 cm) of roots at 45 DAC, from the same explants. The highest survival rate of in vitro regenerated plantlets in the pot was 70.00 % with the stem explants. The results of the current study showed significant increase in the growth of callus of Solanumlycopersicon Mill. Indicating a good efficiency of the optimized media composition and the experimental model used in comparison to other studies of similar nature. Asian J. Med. Biol. Res. December 2015, 1(3): 589-599